1982
DOI: 10.1002/macp.1982.021830203
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic poly[(amino)amide]s and poly(imidazo[4,5‐f]benzimidazole)s derived from poly[(tosylamino)amide]s, 1

Abstract: New poly[(amino)amide]s (4) deriving from 1,2,4,5-benzenetetraamine and terephthalic, isophthalic, or 2,5-furandicarboxylic acid (2ac) were indirectly prepared by detosylation of the corresponding new poly[(tosylamino)amide]s 3, which were obtained by low-temperature solution polymerization of 4,6-ditosylamino-l,3-phenylenediamine (1) with the dicarboxylic acid dichlorides 2a-c. In a subsequent step the poly[(amino)amide]s were converted by polydehydrocyclocondensation into the heat-resistant aromatic poly(imi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…It has been reported that substitution of LL with CL in the feed composition of the reaction could lead to considerable alternations. In comparison to the polyamide homo‐polymerization, the copolymerization happened with a decrease in reaction efficiency and molecular weight . The obtained result might be attributed to the distinct chemical structure of LL and its higher molecular weight compared to CL, which leads to a lower reactivity of LL than CL .…”
Section: Copolymerizationmentioning
confidence: 93%
See 2 more Smart Citations
“…It has been reported that substitution of LL with CL in the feed composition of the reaction could lead to considerable alternations. In comparison to the polyamide homo‐polymerization, the copolymerization happened with a decrease in reaction efficiency and molecular weight . The obtained result might be attributed to the distinct chemical structure of LL and its higher molecular weight compared to CL, which leads to a lower reactivity of LL than CL .…”
Section: Copolymerizationmentioning
confidence: 93%
“…Besides, the type of copolymer and the mean length of similar block units can be obtained from the intensities of carbonyl signals in 13 CNMR spectra. Kehayoglou's measurements on IR absorption spectra confirmed linear characteristic of the polyamide structures, however, due to the substantial similarity observed between PCL and PLL spectra, only the differences between their structures, such as crystallinity were noticeable and there were no detectable peaks associated with the copolymer units in their IR spectra. On the other hand, the absorption peaks of copolymers with high loadings of CL appeared around 700 and 950–980 cm −1 .…”
Section: Copolymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Goodman and Kehayoglou synthesized CoPA6/12 by anionic copolymerization of CL with ω‐laurolactam (LL) at 180°C, using sodium caprolactamate‐N‐phenylcarbamoylcaprolactam as the initiator‐activator system. They characterized the crystallization behavior of the copolymer by differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR) and nuclear magnetic resonance spectroscopy (NMR), and their melting temperature and density measurements indicated a minimum crystallinity with a CL proportion of 50‐60 mol%.…”
Section: Introductionmentioning
confidence: 99%
“…Polybenzimidazoles prepared from 2,5-furandicarboxylic acid chloride (62c) and 1,5-dinaphthylamino-2,4-diaminobenzene with M n of about 10000 and stable up to 400 °C have been prepared and their properties compared with those of the 1,4-phenylic homologues. 209 Other recent studies on furanic polymers prepared by step reactions include the synthesis of polysilylfurylenes, 210 polyimides prepared from furfuryl alcohol oligomers and bis(maleimides) 211 and condensation resins from furfural 212 (41) and hydroxymethylfurfural (47). 213 Ribbon-shaped polymers derived from difuranic compounds and bisdienophiles have been reported.…”
mentioning
confidence: 99%